1984
DOI: 10.1037/0022-0663.76.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Solving arithmetic word problems: Role of reading and computational skills.

Abstract: Investigated how children cope with some of the demands imposed on them by arithmetic word problems by administering problems modeled after those used by the National Assessment of Educational Progress to 200 6th-graders. A computational demand was imposed on the Ss by adding extraneous information to the problems, whereas a reading demand was imposed on them by increasing the syntactic complexity of the problems. Multiple regression analyses indicated that the Ss' computational ability and reading ability tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
4

Year Published

1985
1985
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 11 publications
5
51
0
4
Order By: Relevance
“…This latter finding may imply the existence of a common retrieval component that activates items in long-term memory (cf. Horn 1988) and is consistent with results reported by Muth (1984), who found a moderate relationship (r2 = .37) between reading ability and computational skill. On the other hand, rather than forcing an interpretation on the relation between Addition Efficiency and Reading Skills, we presume that, if a cognitive component score reflecting word retrieval had been available on all subjects, the path from Addition Efficiency to Reading Skills would have been greatly attenuated.…”
Section: Discussionsupporting
confidence: 81%
“…This latter finding may imply the existence of a common retrieval component that activates items in long-term memory (cf. Horn 1988) and is consistent with results reported by Muth (1984), who found a moderate relationship (r2 = .37) between reading ability and computational skill. On the other hand, rather than forcing an interpretation on the relation between Addition Efficiency and Reading Skills, we presume that, if a cognitive component score reflecting word retrieval had been available on all subjects, the path from Addition Efficiency to Reading Skills would have been greatly attenuated.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, striking individual differences exist in manipulating numerical information (e.g., Hunter, 1977). Recognition of memorized series and calculation may well be domain-specific forms of knowledge, but they probably are not task-specific: both procedures may be applicable to a wide variety of tasks that require numerical skills (Holzman et al, 1982;Muth, 1984). In contrast, checking and self-termination are related to efficiency and may well be both task-and domain-independent, but neither characteristic appeared to be related to skill in Experiment 2.…”
Section: Discussionmentioning
confidence: 99%
“…Renninger, Ewen, and Lasher (2002) showed that when the domain is personalized to student's own interests, such as training dogs or ballet turnout, this can potentially limit strategies and mask a lack of knowledge. Part of learning in any domain is distinguishing between relevant and irrelevant information, the addition of extraneous information that might be confused for relevant information can easily increase demand (Muth, 1984).…”
Section: Experiments 3: Specific Familiar Popular Charactermentioning
confidence: 99%